Still proliferating CD44+/Ki67+ tumor cells after neoadjuvant radiochemotherapy identify rectal cancer patients with poor survival - Klose, Johannes; Schmitt, Annelene; Pernthaler, Julia; Warschkow, René; Büchler, Markus W.; Schneider, Martin; Lasitschka, Felix; Tarantino, Ignazio (European journal of surgical oncology, 2021)
Introduction - Distant recurrence, especially liver metastases, occurs in one-third of rectal cancer patients initially treated with curative therapy and is still an unsolved problem. The identification of patients at risk is crucial for enabling individualized treatment. - Material and methods - All patients undergoing curative resection for histologically confirmed rectal cancer after neoadjuvant radiochemotherapy between January 2001 and December 2015 were included. Sections were stained for Ki67, CD44, apoptosis and CD133. Patients were categorized based on whether they were found to have (CD44+/Ki67+) or not have (CD44+/Ki67+) still proliferating tumor cells. - Results - 218 patients who underwent R0 resection for stage I-III rectal cancer were selected. In 37 (17%) of these patients, CD44+/Ki67+ tumor cells were found. In multivariable Cox regression analysis, patients with CD44+/Ki67+ cells had significantly impaired overall (hazard ratio (HR): 3.84, 95% CI: 1.77-8.31, p = 0.001) and relative survival (HR 3.44, 95% CI: 1.46-8.09). The previous results were confirmed after propensity-score matching. In mediation-analysis, the presence of CD44+/Ki67+ cells was associated with a substantial direct effect on overall (HR 1.92, 95% CI: 1.09-9.28) and relative survival (HR 1.63, 95% CI: 1.31-6.38). - Conclusions - The presence of still proliferating CD44+/Ki67+ tumor cells after neoadjuvant radiochemotherapy was associated with impaired oncological long-term outcomes. Characterization of these cells should be performed.
Gesehen am 20.12.2021
Im Titel sind die Zeichen "+" hochgestellt